Control of Glare for VDT Operators: Evaluation of Different Lenses by Subjects - Mousa, G.Y.; Woodruff, M.E. (Canadian Journal of Optometry, 2021)
The widespread use of video display terminals (VDTs) in offices has been accompanied by many complaints of visual problems. A recent study by the Canadian Labour Congress on vision problems among 2,300 office workers showed that VDT operators report twice as many vision problems and require more frequent changes in lens prescription. Visual complaints have stimulated research into new means of relieving the discomfort experienced by VDT operators.